Endemic Cardiovascular Diseases of the Poorest Billion. Issue 24 (14th June 2016) - Kwan, Gene F.; Mayosi, Bongani M.; Mocumbi, Ana O.; Miranda, J. Jaime; Ezzati, Majid; Jain, Yogesh; Robles, Gisela; Benjamin, Emelia J.; Subramanian, S. V.; Bukhman, Gene
Abstract : The poorest billion people are distributed throughout the world, though most are concentrated in rural sub-Saharan Africa and South Asia. Cardiovascular disease (CVD) data can be sparse in low- and middle-income countries beyond urban centers. Despite this urban bias, CVD registries from the poorest countries have long revealed a predominance of nonatherosclerotic stroke, hypertensive heart disease, nonischemic and Chagas cardiomyopathies, rheumatic heart disease, and congenital heart anomalies, among others. Ischemic heart disease has been relatively uncommon. Here, we summarize what is known about the epidemiology of CVDs among the world's poorest people and evaluate the relevance of global targets for CVD control in this population. We assessed both primary data sources, and the 2013 Global Burden of Disease Study modeled estimates in the world's 16 poorest countries where 62% of the population are among the poorest billion. We found that ischemic heart disease accounted for only 12% of the combined CVD and congenital heart anomaly disability-adjusted life years (DALYs) in the poorest countries, compared with 51% of DALYs in high-income countries. We found that as little as 53% of the combined CVD and congenital heart anomaly burden (1629/3049 DALYs per 100 000) was attributed to behavioral or metabolic risk factors in the poorest countries (eg, in Niger, 82% of the population among the poorest billion) compared with 85% of the combined CVD and congenital heart anomaly burden (4439/5199 DALYs) in high-income countries. Further, of the combined CVD and congenital heart anomaly burden, 34% was accrued in people under age 30 years in the poorest countries, while only 3% is accrued under age 30 years in high-income countries. We conclude although the current global targets for noncommunicable disease and CVD control will help diminish premature CVD death in the poorest populations, they are not sufficient. Specifically, the current framework (1) excludes deaths of people <30 years of age and deaths attributable to congenital heart anomalies, and (2) emphasizes interventions to prevent and treat conditions attributed to behavioral and metabolic risks factors. We recommend a complementary strategy for the poorest populations that targets premature death at younger ages, addresses environmental and infectious risks, and introduces broader integrated health system interventions, including cardiac surgery for congenital and rheumatic heart disease. Abstract : Supplemental Digital Content is available in the text.